Investigating the Nature of Growth-Environment Relationship for India - Haque, Mohammad Imdadul; Asif, Mohammad; Tausif, Mohammad Rumzi; Khan, Mohd Naved (International Journal of Energy Economics and Policy, 2024)
Environmental concerns need to be addressed to make economic growth sustainable. Theories in the literature attempt to establish the relationship between economic growth and environmental degradation. These theories are not deterministic, as concepts like the inverted U-shaped or N-shaped Environmental Kuznets Curve (EKC) have yielded different results for different economies. This study attempts to validate the shape of the EKC and simultaneously test for an asymmetric relationship between economic growth and carbon dioxide emissions. To achieve this, the study uses the simple and non-linear Autoregressive Distributed Lag (ARDL) method on data from 1965 to 2021. The study finds evidence of an inverted U-shaped EKC but finds no evidence of an N-shaped EKC for India. Additionally, the study reports an asymmetric relationship between economic growth, energy consumption, and carbon dioxide emissions. Based on these findings, the study provides suitable policy recommendations.